Mourning and the COVID-19 Pandemic: A Literature Study - Fanny Eka Putri*; Achmad Chusairi (Riwayat: Educational Journal of History and Humanities, 2023)
The COVID-19 pandemic has caused many crises in various parts of the world, including in Indonesia itself. The various crises caused by the pandemic include social restrictions, changes in the education system, many individuals who have lost their jobs, and the most severe is the number of deaths. This article uses a systematic literature review method using 10 articles consisting of 2 articles obtained through the Science Direct site (sciencedirect.com), 4 articles obtained through the SAGE site (journals.sagepub.com), 4 articles obtained through the ResearchGate site (researchgate.net). This article wants to see how the process experienced by individuals who are grieving as a result of the loss of a loved one during the COVID-19 pandemic. The results of the literature review show that the process of grief experienced by individuals during the COVID-19 period has become more complex and longer. This mourning process is caused by two things, namely the limitation of social interaction that makes individuals have to go through the mourning process without physical or emotional support from relatives and the limited implementation of the funeral process which creates special pressure for individuals who are left behind because they cannot pay their last respects to loved ones who have passed away.